The length of spells of unemployment in ireland - Omahony, M (Economic & Social Studies, 1983)
Abstract- This paper examines the average length of a spell of unemployment in the Irish Republic. The analysis is conducted using two measures, one emphasising the flow of persons into unemployment and the other concentrating on the stock of currently unemployed individuals. These measures imply long average durations for the unemployed in Ireland both in absolute terms and relative to their British counterparts. Some of the traditional structural aspects of Irish unemployment, i.e., the high proportion of unskilled, elderly or regionally disadvantaged persons among the unemployed, provide a partial explanation of these long spell lengths.
Keywords: Economics; Sociology